N-acetyl-p-benzoquinone imine: a cytochrome P-450-mediated oxidation product of acetaminophen. - Dahlin, D C (1984)
N-acetyl-p-benzoquinone imine (NAPQI) has been proposed as the toxic metabolite of acetaminophen for the past 10 years, although it has never been detected as an enzymatic oxidation product of acetaminophen. We report (i) direct detection of NAPQI formed as an oxidation product of acetaminophen by cytochrome P-450 and cumene hydroperoxide and (ii) indirect evidence that is compelling for NAPQI formation from acetaminophen by cytochrome P-450, NADPH, and NADPH-cytochrome P-450 reductase. Evidence is provided for the rapid reduction of NAPQI back to acetaminophen by NADPH and NADPH-cytochrome P-450 reductase such that steady-state levels of NAPQI were below our detection limits of 6.7 X 10(-8) M. In mouse liver microsomal incubations, radiolabeled analogs of both NAPQI and acetaminophen bound covalently to microsomal protein with the loss of approximately equal to 20% of the acetyl group as acetamide. The binding in each case was decreased by glutathione with concomitant formation of 3-S-glutathionylacetaminophen. The binding also was decreased by L-ascorbic acid, NADPH, and NADH with reduction of NAPQI to acetaminophen. Results of partitioning experiments indicate that NAPQI is a major metabolite of acetaminophen, a considerable fraction of which is rapidly reduced back to acetaminophen.